2019
DOI: 10.1186/s12885-019-6207-y
|View full text |Cite
|
Sign up to set email alerts
|

Cooperation of Dnmt3a R878H with Nras G12D promotes leukemogenesis in knock-in mice: a pilot study

Abstract: BackgroundDNMT3A R882H, a frequent mutation in acute myeloid leukemia (AML), plays a critical role in malignant hematopoiesis. Recent findings suggest that DNMT3A mutant acts as a founder mutation and requires additional genetic events to induce full-blown AML. Here, we investigated the cooperation of mutant DNMT3A and NRAS in leukemogenesis by generating a double knock-in (DKI) mouse model harboring both Dnmt3a R878H and Nras G12D mutations.MethodsDKI mice with both Dnmt3a R878H and Nras G12D mutations were g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…The Dnmt3aR878H/WT KI mice were crossed with NrasG12D/WT KI mice to generate the DKI mouse model (Mx1-Cre; Dnmt3aR878H/WT; NrasG12D/WT). DKI mice developed more aggressive AML than Dnmt3aR878H/WT KI mice after PIpC induction [16]. Since most leukemic cells were Gr1+ cells in the AML mice, we further analyzed the RNA-sequencing data (Supplementary Tables 1-3) of Gr1+ bone marrow cells and revealed that 1,129 genes were differentially expressed in DKI mice versus wild type mice.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The Dnmt3aR878H/WT KI mice were crossed with NrasG12D/WT KI mice to generate the DKI mouse model (Mx1-Cre; Dnmt3aR878H/WT; NrasG12D/WT). DKI mice developed more aggressive AML than Dnmt3aR878H/WT KI mice after PIpC induction [16]. Since most leukemic cells were Gr1+ cells in the AML mice, we further analyzed the RNA-sequencing data (Supplementary Tables 1-3) of Gr1+ bone marrow cells and revealed that 1,129 genes were differentially expressed in DKI mice versus wild type mice.…”
Section: Resultsmentioning
confidence: 99%
“…Generation of AML mouse models and transcriptomic analysis. The conditional knock-in AML mouse models harboring Dnmt3aR878H/WT, NrasG12D/WT and both mutations were established respectively as previously described [16]. Mice were used according to animal care standards.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast to Nras G12D/+ alone or p53 −/− alone, cooperation of these mutations induces quiescence in megakaryocyte-erythroid progenitors (MEPs) that is sufficient to drive AML development in mice ( Table 2 ; Supplementary Figure S3 ) [ 127 ]. Similarly, cooperation of the NrasG12D mutation with Dnmt3aR878H/DNMT3AR882H activates the Myc pathway and induces AML in mice ( Table 2 ; Supplementary Figure S3 ) [ 128 , 132 ]. NRAS mutations also show synergistic AML development with mutations in other genes such as NPM1 [ 129 ], EZH2 [ 130 ], and IDH2 [ 25 ] ( Table 2 ; Supplementary Figure S3 ).…”
Section: Mouse Models Of Genes Involved In Cell Signaling Pathways In Myeloid Malignanciesmentioning
confidence: 99%